On one model approach to stock assessment for red king crab Paralithodes camtschaticus on the shelf of West Kamchatka - Oleg I. Ilyin; Pavel Yu. Ivanov (Известия ТИНРО, 2015)
A possible model approach to stock assessment of marine commercial invertebrates is discussed based on modeling of year-to-year dynamics for three functional groups (recruits, prerecruits, and commercial males). The model parameters are determined by joint solution of the tasks of optimal filtration and identification. As an example, this approach is used for assessment of the stock of king crab on the shelf of West Kamchatka. For this case, the data on actual catch are used obtained from reports of customs in Japan, Korea, USA, and China about the volume of crab products imported from Russia. The modeling confirms the conclusion from direct observations about rapid growth of the red king crab stock at West Kamchatka in recent years. Following to these results, the value of total allowable catch (TAC) can be substantially increased for this species. The officially recommended TAC of red king crab at West Kamchatka for 2016 is below of the 95 % confidence interval of the really possible catch. This value does not account the species stock recovery and hamper rational utilization of the valued natural resource.